Central pontine myelinolysis and its differential diagnoses in a pregnant woman with diabetes: case report and literature review - Danielle Medeiros Urquiza; Alex Sandro Rolland Souza; Giovanna Macedo Tavares; Gustavo Fonseca de Albuquerque Souza; Leila Katz (Revista Brasileira de Saúde Materno Infantil)
Abstract Introduction: central pontine myelinolysis (CPM) is characterized by the destruction of the myelin sheath from oligodendrocytes due to a rapid increase in plasma osmolarity and consequent passage of components through the blood-brain barrier. Description: a woman at six weeks of pregnancy, presenting previous uninvestigated generalized tonic-clonic seizures, type 1 diabetes mellitus since childhood, and using both licit and illicit drugs, was admitted to the hospital with CPM diagnosed after dysglycemia. She presented an unfavorable obstetric outcome with a neurological rehabilitation prognosis. Discussion: the rapid correction of hyponatremia is considered the main cause of CPM among its different etiologies described in the literature, such as relevant dysglycemia, nutritional deficiencies, and drug abuse. This study reported differential diagnoses of CPM in an atypical context (i.e., pregnancy), emphasizing the importance of knowing this multifactorial condition in intensive and obstetric care for appropriate multi-professional clinical management.